2015
DOI: 10.1002/jat.3233
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and toxicity of spherical aluminum oxide nanoparticles

Abstract: With the rapid development of the nano-industry, concerns about their potential adverse health effects have been raised. Thus, ranking accurately their toxicity and prioritizing for in vivo testing through in vitro toxicity test is needed. In this study, we used three types of synthesized aluminum oxide nanoparticles (AlONPs): γ-aluminum oxide hydroxide nanoparticles (γ-AlOHNPs), γ-and α-AlONPs. All three AlONPs were spherical, and the surface area was the greatest for γ-AlONPs, followed by the α-AlONPs and γ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 38 publications
3
36
1
Order By: Relevance
“…Similarly, aluminum‐induced brain damage altered the level of antioxidant elements in the brain (Solfrizzi et al, ; Tripathi et al, ), and pulmonary exposure to AlONPs induced the inflammatory response with oxidative stress (Lu et al, ). Additionally, in our previous studies, AlONPs influenced the tissue homeostasis of redox reaction‐related trace elements, including Mn, Zn, Cu and Fe (Park, Sim, et al, ; Park, Kim, et al, ; Park, Lee, et al, ). In the present study, we also found that the level of redox‐reaction‐related trace elements in tissues was altered after exposure to the three types of AlONPs.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Similarly, aluminum‐induced brain damage altered the level of antioxidant elements in the brain (Solfrizzi et al, ; Tripathi et al, ), and pulmonary exposure to AlONPs induced the inflammatory response with oxidative stress (Lu et al, ). Additionally, in our previous studies, AlONPs influenced the tissue homeostasis of redox reaction‐related trace elements, including Mn, Zn, Cu and Fe (Park, Sim, et al, ; Park, Kim, et al, ; Park, Lee, et al, ). In the present study, we also found that the level of redox‐reaction‐related trace elements in tissues was altered after exposure to the three types of AlONPs.…”
Section: Discussionmentioning
confidence: 83%
“…However, it is well known that the properties of NPs are rapidly altered in biological fluids, thus NPs can induce different toxicity with that expected in the manufactured condition within the biological system (Higashisaka, Nagano, Yoshioka, & Tsutsumi, ; Nel et al, ). For example, in our previous study, the accumulation and toxicity of spherical AlONPs were more marked in mice exposed to γ‐aluminum oxide hydroxide NPs compared with those of γ‐AlONPs and α‐AlONPs due to their low stability within biological systems (Park, Lee, et al, ), and the surface coating of Zn oxide NPs with phosphate and sulfide, which have very low solubility in water, did not attenuate tissue distribution and toxicity of Zn oxide NPs following 28 days of oral administration due to the higher particlization rate of Zn oxide NPs in the intestine (Park, Jeong, Yoon, & Kim, ). Additionally, the inflammatory response produced in cells exposed to AlONPs (50 and 80 nm) depended on the surface area dose instilled, but not the mass dose instilled, emphasizing the importance of media‐ and temperature‐dependent particle agglomeration levels in assessing the biological safety of nanomaterials (Duffin, Tran, Brown, Stone, & Donaldson, ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…AlONPs are less toxic than other metal-based nanomaterials. However, AlONPs have been demonstrated to induce cell death by impairing cellular components, both in-vivo and in-vitro [11]. In a study of Park et al, three different types of AlONPs, α-AlONPs and γ-AlONPs, and aluminum oxide hydroxide nanoparticles (γ-AlOHNPs) were synthesized and their distribution and biological responses in vivo (5 and 10 mg.kg -1 ) were compared.…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
“…The results demonstrated that γ-AlOHNPs caused the highest toxicity. Thus, the presence of hydroxyl groups is an important factor in determining the toxicity of AlONPs [11]. In a study of Prakash et al, AlONPs which were synthesized using microemulsion hindered the growth and multiplication of the tested bacteria, including highly multiresistant bacteria (Klebsiella Pneumonia, Salmonella typhi, and Vibrio cholera).…”
Section: Metal Nanoparticlesmentioning
confidence: 99%